PENERAPAN METODE STRUKTURAL ANALITIK SINTETIK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA SISWA TUNAGRAHITA RINGAN - Alfiani Umayya; Ediyanto Ediyanto; Usep Kustiawan (Universitas Muria Kudus, 2023)
The purpose of this study was to determine the increase in the beginning reading ability of students with mild mental retardation by using a synthetic structural analytic method.The research method used was a pre-experimental design with a one-group-pretest-posttest research design and using the Wilcoxon matched pairs data analysis method. The sample in this study were all students with mild mental retardation at SDLB Sumber Dharma Malang, totaling 5 students.The results showed that there was an increase in the average score from pretest 58 to posttest 93 in students' reading ability. The results of the hypothesis test showed that there was a significant difference 0.041 0.05, the Asymp.sig value 0.05, then it was rejected and accepted, meaning that there was a significant increase in initial reading ability using synthetic structural analytic methods for mild mentally retarded students at SDLB Sumber Dharma Malang City.